2021
DOI: 10.1088/1742-6596/1863/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Handling Missing Values and Unusual Observations in Statistical Downscaling Using Kalman Filter

Abstract: Rainfall forecasting model using data Global Circular Model (GCM) with Statistical Downscaling technique has a fairly high accuracy. However, missing local climate information poses a constraint in data analysis and forecasting. Missing value imputation is one solution that can be used. Kalman Filter Imputation and State Space Model Arima are imputation methods that operate recursively where there is an update of prediction values when data updates occur. This study aimed to find the best model to use for miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Therefore, it is required to interpolate and smooth the values of time series to fill the gaps of the missing values. Here, it worth highlighting that previous works have shown that the Kalman filter produces appropriate and efficient values compared to other interpolation methods [23][24][25].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, it is required to interpolate and smooth the values of time series to fill the gaps of the missing values. Here, it worth highlighting that previous works have shown that the Kalman filter produces appropriate and efficient values compared to other interpolation methods [23][24][25].…”
Section: Introductionmentioning
confidence: 96%
“…For handling missing values in the produced time series, the Kalman smoothing filter [23,34] was evaluated and compared to regression analysis using the Cook's distance and Hat matrix. Annual density plots helped initial observations on the completed LST and NDVI time series, while the additive seasonal decomposition model and the BFAST algorithm served as tools for analyzing the time series and detecting breakpoints.…”
Section: Introductionmentioning
confidence: 99%
“…50 Here we replace the missing data in all EPA sites, and PA sensors using the ARIMA model with Kalman filter. [51][52][53][54] The power spectral density of each EPA and PA hourly time series of PM 2.5 data was then calculated using the stats package in R.…”
Section: Spectral Analysis: Methodsmentioning
confidence: 99%
“…We cannot impute these values using ARIMA, (e.g. Saputra et al 2021) and NN-techniques (e.g. Li et al 2020;Shu et al 2021), as the SRNN would not then need to learn how to fill the gaps.…”
Section: Parameter Configurationmentioning
confidence: 99%